Ethnomathematics in Fraction Numeracy Ability of Fifth-Grade Students in The Merdeka Curriculum - Rosid, Asri Ananda Afsari A; Alfiandri, Heru (International Conference on Elementary Education, 2024)
Efforts to improve educational services in the 5.0 era have been developed by implementing a Merdeka curriculum. In its implementation, learning is expected to be student-centered with the hope that each student will achieve minimum competencies, including numeracy and literacy competencies, without losing national identity. Low student learning outcomes in problem-solving abilities on fractions result in an incomplete understanding of the concept, so students need to be trained in critical thinking. This research aims to describe ethnomathematics in students’ fraction numeration abilities in the Merdeka curriculum using qualitative methods with a hermeneutic phenomenology type involving five people out of 26 fifth-grade students and mathematics teachers. Data was collected using written tests and interviews with participants and processed using Moustaka’s analysis stages and Paul Ricoeur’s interpretation theory. The research results through trials and interviews show that 3 out of 5 students already understand the prerequisite fraction material and can solve simple fraction problems based on ethnomathematics. However, these five students had obstacles in solving fraction calculation operation problems. Apart from that, the results of teacher interviews show that learning focuses on cultivating concepts without contextually involving culture. Research can be concluded as a constructive reference for improving fraction numeration skills through ethnomathematics in the Merdeka curriculum.